A QUALITATIVE CASE STUDY ON STUDENTS’ STRATEGIES IN OVERCOMING SPEAKING CHALLENGES AT THE TENTH GRADE OF ONE OF SENIOR HIGH SCHOOL IN KARAWANG - Diannisa Istighfarina; Iwan Ridwan; Fela Dafitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to identify the speaking difficulties experienced by tenth-grade students at One of Senior High School in Karawang and to explore the strategies they used to overcome those difficulties. Employing a qualitative approach with a case study design, this study involved six tenth-grade students selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using thematic analysis proposed by Braun and Clarke (2006). The findings revealed that students encountered various speaking difficulties, which could be categorized into linguistic and psychological factors. Linguistic challenges included limited vocabulary and pronunciation problems, while psychological difficulties involved fear of making mistakes, lack of confidence, and speaking anxiety. Despite these challenges, students employed several strategies to improve their speaking ability, including watching English videos and listening to English songs, memorizing vocabulary, using digital tools such as Google Translate, practicing independently in front of a mirror. These strategies reflected cognitive, memory, compensation, affective, and social strategies as proposed by Oxford (1990). The findings suggest that students are active learners who employ various strategies to cope with speaking difficulties. Therefore, English teachers are encouraged to provide supportive learning environments and meaningful speaking opportunities to enhance students’ communicative competence.